The Indian Forester (August 2019) / edited by Arun Singh Rawat. - Forest Research Institute; Rawat, Arun Singh (Dehradun : Forest Research Institute, 2019)
The Indian Forester is the oldest Journal on tropical forestry, published since July, 1875, initially as quarterly and later from January, 1883 as monthly journal.
Keywords: Forest Journal, India